How do external donors influence national health policy processes? Experiences of domestic policy actors in Cambodia and Pakistan - Khan, Mishal S (Health Policy Plan, 2018)
Although concerns have historically been raised about the influence of external donors on health policy process in recipient countries, remarkably few studies have investigated perspectives and experiences of domestic policymakers and advisers. This study examines donor influence at different stages of the health policy process (priority setting, policy formulation, policy implementation and monitoring and evaluation) in two aid-dependent LMICs, Cambodia and Pakistan. It identifies mechanisms through which asymmetries in influence between donors and domestic policy actors emerge. We conducted 24 key informant interviews—14 in Pakistan and 10 in Cambodia—with high-level decision-makers who inform or authorize health priority setting, allocate resources and/or are responsible for policy implementation, identifying three routes of influence: financial resources, technical expertise and indirect financial and political incentives. We used both inductive and deductive approaches to analyse the data. Our findings indicate that different routes of influence emerged depending on the stage of the policy process. Control of financial resources was the most commonly identified route by which donors influenced priority setting and policy implementation. Greater (perceived) technical expertise played an important role in donor influence at the policy formulation stage. Donors’ power in influencing decisions, particularly during the final (monitoring and evaluation) stage of the policy process, was mediated by their ability to control indirect financial and political incentives as well as direct control of financial resources. This study thus helps unpack the nuances of donor influence over health policymaking in these settings, and can potentially indicate areas that require attention to increase the ownership of domestic actors of their countries’ health policy processes.